Priming Adult Learners for Learning Transfer: Beyond Content and Delivery. Issue 1 (February 2019) - Roumell, Elizabeth Anne
In adult education, we have skilled instructional designers, expertise in structuring learning events and delivering content, and we have robust learning theories to draw from, and yet the effective transfer of learning still seems elusive. Recent literature reviews on learning transfer indicate that a large percentage of adult learning does not successfully transfer. The research also suggests transfer needs to be supported at the individual, instructional, and organizational levels. Conventional educational practices often do not provide sufficient scaffolding and social learning to promote learning transfer processes beyond the initial learning event. This article discusses three practices to support mindful learning transfer at each of these levels. Educators are not only responsible for designing and delivering learning content but also scaffolding meaningful social interactions and the development of transfer skills.